Bioagent mediated management of citrus canker - SAIKIA, SWAGATA; BORA, POPY; BORA, L C (The Indian Journal of Agricultural Sciences, 2021)
Citrus canker caused by Xanthomonas citri pv. citri (Xcc) is one of the most destructive diseases of citrus. We investigated the citrus canker disease management in Experimental Farm of AAU, Jorhat, Assam (2017-19) using three microbial bioformulations, viz. Biogreen-5 (Combination of Pseudomonas fluorescens, Bacillus thuringiensis, Beauveria bassiana, Metarhizium anisopliae and Trichoderma viride), Bioveer (Trichoderma viride) and Biosona (Beauveria bassiana) in Assam lemon (Citrus limon L. Burm. f ) as a test crop, a premier commercial citrus cultivar of Assam. These bioformulations were observed highly effective in suppressing citrus canker incidence and enhancing fruit yield. Biogreen-5 applied as soil application as well as foliar spray showed maximum reduction in canker incidence (35.55-20.96%) coupled with an enhanced fruit yield (12.43-41.93%). Enhancement of the population count of phylloplane as well as rhizosphere microbes were conspicuously observed in plants treated with microbial bioformulations, offering an environmentally benign alternative of canker management of Assam lemon.